Mud, memories, and meaning: Investigating climate security in Southwestern Zimbabwe - Maviza, Gracsious; Taiwo, Ibukun (2025)
This study examines climate security challenges in southwestern Zimbabwe's Tsholotsho district, where communities continue to grapple with the lasting impacts of Cyclones Dineo (2017) and Idai (2019), compounded by severe drought in 2024. Researchers from the CGIAR Climate Security Southern Africa Hub conducted immersive fieldwork in late 2024, living alongside local communities in wards 5, 6, 8, and 10 to understand how climate stresses interact with social tensions and resource conflicts.